Rapid On-Site Evaluation With Telecytology Significantly Reduced Unsatisfactory Rates of Thyroid Fine-Needle Aspiration: A Case-Control Study. Issue 3 (19th October 2019) - Lin, Diana M; Tracht, Jessica; Rosenblum, Frida; Kouba, Erik; Bahl, Deepti; Patel, Anish; Eltoum, Isam-Eldin
Abstract: Objectives: We evaluated telecytology rapid on-site evaluation (ROSE) for thyroid ultrasound-guided fine-needle aspiration. To the best of our knowledge, this study is the first case-control clinical trial of thyroid telecytology. Methods: We introduced on-site ROSE in our institution's thyroid clinic for 6 months, followed by telecytology for 12 months. Our institution's ultrasound clinic, where ROSE is not provided, was used as a control group for each period. Results: Both groups had similar initial unsatisfactory rates (thyroid clinic: 8.8%; ultrasound clinic: 8.0%) before the study began. The thyroid clinic's unsatisfactory rate was significantly reduced to 1.6% after on-site ROSE ( P = .001) and to 3.8% after telecytology ROSE ( P = .010), with no significant difference between on-site and telecytology ROSE periods ( P > .05). The ultrasound clinic's unsatisfactory rate was unchanged for both periods. Concordance between telecytology ROSE and final adequacy was 97% (κ = 0.699). Conclusions: Telecytology ROSE reduces unsatisfactory rates for ultrasound-guided fine-needle aspiration without compromising patient care.